2012
DOI: 10.3329/agric.v10i1.11064
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Garlic Extract, Allamanda Leaf Extract and Provax -200 on Seed Borne Fungi of Rice

Abstract: Seeds of rice were treated with Garlic (Allium sativum) clove extract @ 1:0, 1:1, 1:2 dilutions in water, allamanda (Allamanda cathartica) leaf extract @ 1:1, 1:2, 1:3 dilutions in water and Provax-200 @ 0.3% for controlling seed borne fungi, where the seed samples of three rice varieties viz. Katharee, Gutee Aus and Kalijira were collected from farmer’s storages of Bangladesh. The seed germination under control ranged from 64 to 77%, where treatments resulted up to 100% germination. The identified seed borne … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 5 publications
0
7
0
1
Order By: Relevance
“…Mohana et al (2011) from India reported that methanol extract of Acacia nilotica, Caesalpinia coriaria, Decalepis hamiltonii, Emblica officinalis, Lawsonia inermis and Mimosops elengi showed significant antifungal activity at 3500 µg/ml concentration on seed pathogens viz., Alternaria alternata, Aspergillus flavus, Curvularia lunata, Drechslera oryzae, D. halodes, Fusarium moniliforme, Pyricularia oryzae and Trichoconis padwickii by poisoned food technique. Yeasmin et al (2012) reported that seed borne fungi of rice were Bipolaris oryzae, Curvularia oryzae, Fusarium oxysporum, F. moniliforme, Nigrospora oryzae, Aspergillus flavus, A. niger and Penicillium sp., where prevalence of Bipolaris oryzae (7.5%) and F. moniliforme (8.3%) were the maximum. All the treatments significantly reduced the seed borne fungi up to 100% over the control, where Provax was found best and was significantly similar to garlic (1 : 1) extract against seed borne pathogens of rice.…”
Section: Resultsmentioning
confidence: 99%
“…Mohana et al (2011) from India reported that methanol extract of Acacia nilotica, Caesalpinia coriaria, Decalepis hamiltonii, Emblica officinalis, Lawsonia inermis and Mimosops elengi showed significant antifungal activity at 3500 µg/ml concentration on seed pathogens viz., Alternaria alternata, Aspergillus flavus, Curvularia lunata, Drechslera oryzae, D. halodes, Fusarium moniliforme, Pyricularia oryzae and Trichoconis padwickii by poisoned food technique. Yeasmin et al (2012) reported that seed borne fungi of rice were Bipolaris oryzae, Curvularia oryzae, Fusarium oxysporum, F. moniliforme, Nigrospora oryzae, Aspergillus flavus, A. niger and Penicillium sp., where prevalence of Bipolaris oryzae (7.5%) and F. moniliforme (8.3%) were the maximum. All the treatments significantly reduced the seed borne fungi up to 100% over the control, where Provax was found best and was significantly similar to garlic (1 : 1) extract against seed borne pathogens of rice.…”
Section: Resultsmentioning
confidence: 99%
“…Radhika and Nasreen [28] and Tamil et al recorded carbohydrates, steroids, alkaloids, proteins, flavonoids, terpenoids, phenolics, tannins and glycosides [29] . Aqueous, extract showed alkaloids, flavonoids, saponins and carbohydrates [30] ; and petroleum ether, chloroform, ethanol, acetone analysis of phytochemical constituents of A. cathartica flower by Joselin et al revealed phenolic compounds, flavonoids, saponins, glycosides, terpenoids, steroids, coumarins, quinones, phytosterols, carbohydrates with no traces of alkaloids and proteins [31] .…”
Section: Discussionmentioning
confidence: 99%
“…Alternaria alternata, Aspergillus flavus, Curvularia lunata, Drechslera oryzae, D. halodes, Fusarium moniliforme, Pyricularia oryzae and Trichoconis padwickii by poisoned food technique. Yeasmin et al (2012) reported seed borne fungi of rice, namely Aspergillus flavus, A. niger, Bipolaris oryzae, Curvularia oryzae, Fusarium oxysporum, F. moniliforme, Nigrospora oryzae, and Penicillium sp., where prevalence of Bipolaris oryzae (7.5%) and F. moniliforme (8.3%) were the maximum. They treated the fungi with Provax and garlic extract and observed that due to treatment the seed borne fungi was reduced up to 100% over the control.…”
Section: -T I =mentioning
confidence: 99%